Madhyarātera hatyākāṇḍa - Tāreka, Sāīda (Deoẏāna Moḥ. Ābeda Ālī : paribeśaka Jharṇādhārā Sāhitya Parishada, 1979)
Account of the conspiracy leading to the assassination of Sheikh Mujibur Rahman, 1922-1975, former president of Bangladesh.